2009
DOI: 10.1016/j.vascn.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of BrdU incorporation as a high-throughput method for measuring adult neurogenesis in the mouse

Abstract: Introduction-The generation of new neurons occurs throughout adulthood in discrete brain regions, and may be regulated by neuropsychiatric diseases and therapeutic drug treatments. Most current methods that study this process measure the labeling of newborn cells by 5-bromo-2-deoxyuridine (BrdU) using immunohistochemical methods followed by the microscopic counting of BrdU positive cells. This method is time consuming and labor intensive, typically taking several weeks to analyze.Methods-Therefore, we characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…Background signal was accounted for using stained tissue from untreated animals that did not receive BrdU injections. We have previously shown that experimental results obtained with this method are essentially similar to those obtained using immunohistochemistry (Balu et al 2009). …”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Background signal was accounted for using stained tissue from untreated animals that did not receive BrdU injections. We have previously shown that experimental results obtained with this method are essentially similar to those obtained using immunohistochemistry (Balu et al 2009). …”
Section: Methodssupporting
confidence: 62%
“…; Roche Applied Sciences, Indianapolis, IN), dissolved in 0.9% saline, 24 hours prior to sacrifice. Labeling of BrdU was measured in dissociated hippocampal cells displaying the nuclear marker 7-aminoactinomycin D (7-AAD) by flow cytometry as previously described and validated by immunohistochemistry (Balu et al 2009). In brief, mice were decapitated and both hippocampal lobes were dissected on ice and then underwent mechanical trituration to make a single-cell suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies have revealed that a single intrahippocampal injection of a β 3 -adrenergic receptor (β 3 -AR) agonist into the brain or systemic administration over 7 days of isoproterenol, a nonselective β-AR agonist, increases proliferation in the DG and leads to higher number of nestin + GFAP + cells (Jhaveri et al, 2010). Ablation of noradrenergic neurons leads to reduced proliferation of progenitor cells in the SGZ, although proliferation in the SVZ remains unchanged after such injury (Kulkarni et al, 2002;Balu et al, 2009). These studies indicate different responses of progenitor cells to noradrenaline signaling, depending on their location in the brain.…”
Section: Noradrenalinementioning
confidence: 99%
“…It is postulated that the changes in the mobilization of neurotrophins in turn lead to increased neurogenesis thought to repair damage and restore hippocampal function. A minimum of 2 weeks of continuous treatment with antidepressants is necessary to increase neurogenesis in the hippocampus because a single acute treatment or continuous treatment up through 7 days does not alter cell proliferation (Balu et al, 2009b;Wu and Castrén, 2009). Long-term treatment with fluoxetine or other antidepressants is also necessary to alter brain-derived neurotrophic factor (BDNF) levels as acute administration does not alter protein or mRNA levels of BDNF in the hippocampus (Nibuya et al, 1995;Balu et al, 2008).…”
mentioning
confidence: 99%